MANAJEMEN DAKWAH DAN KOMUNIKASI POLITIK DI ERA SOCIETY 5.0 (AT-TAWASUL, 2026)
The development of Society 5.0 marks a fundamental shift in how society produces, disseminates, and interprets political and da'wah messages. Digital technology fosters the formation of an intense two-way communication space, where interactions between political actors and the public take place more directly through social media. This phenomenon strengthens the political participation of the younger generation and accelerates the flow of information, but simultaneously raises the risk of polarization, misinformation, and manipulation of public perception. These dynamics are further complicated by the frequent intrusion of identity politics and the use of religious symbols into political communication. Digital da'wah is also undergoing a transformation: religious messages are disseminated massively and rapidly, but are vulnerable to being drawn into specific political interests. Therefore, the management of da'wah and political communication requires a more ethical and adaptive approach to ensure that technology serves to strengthen humanitarian values, religious moderation, and democratic integrity. Harmonious integration between da'wah, politics, and technology is crucial so that the digital space becomes not merely an arena for contestation of interests, but also a vehicle for public education and strengthening social governance